Losing the other; Education for Life; Kenny G. [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1993)
Summary: Presents the cry for justice of victims, Levi and Alvin Vinculado in Bulacan; the female functional literacy program launched by UNICEF together with DECS in Maguindanao; and the one-on-one interview withKenny G., a famous saxophone player.
Contents: Losing the other (20 min.) -- Education for Life (15 min.) -- Kenny G. (15 min.)
VHS.
Credits: Reporters, Cheche Lazaro and Marga Ortegas.
Keywords: Kenny G. -- Interviews; Offenses against the person -- Philippines -- San Ildefonso (Bulacan).; Adult education -- Philippines -- Maguindanao; Literacy -- Government politic -- Philippines -- Maguindanao